Prevalence and species identification of trematode metacercariae in Qiqihar, Northeast China - Zhang, Fengyu; Li, Jianke; Zhang, Shaocheng; Chen, Ting; Zhang, Hao (Frontiers in Microbiology, 2024)
Fish-borne trematode (FBT) is an important group of parasites that are endemic worldwide to a certain extent. However, despite the epidemiological significance, the species and phylogenetic evolution characteristics of FBT metacercariae have not been well studied. In this study, a total of 600 Pseudorasbora parva (P. parva) specimens were collected from Qiqihar, 61.8% (371/600) were found to be infected with trematode metacercariae. A total of three kinds of trematodes metacercariae were obtained, they were identified as Clonorchis sinensis (C. sinensis), Metorchis orientalis (M. orientalis) and Metorchis taiwanensis (M. taiwanensis) by morphlogical and phylogenetic analysis with infection rates of 47.7% (286/600), 15.5% (93/600) and 23.7% (142/600), respectively. Meanwhile, survey of the three trematodes metacercariae showed that the infection rate of C. sinensis metacercariae was the highest in September, up to 66% (66/100), and the lowest in June at 26% (26/100); The infection rate of M. orientalis metacercariae was the highest in October at 26% (26/100), and the lowest in June at 5% (5/100); the infection rate of M. taiwanensis metacercariae was at its peak in November at 36% (36/100) and the lowest in July at 15% (15/100). The co-infection of metacercariae of C. sinensis and M. taiwanensis was the most common and reached a peak in October and their infection rate was higher in autumn than in summer. The peak of infection intensity of metacercariae for C. sinensis, M. orientalis and M. taiwanensis were different: C. sinensis was 24/g in September, M. orientalis was 7/g in October and M. taiwanensi was 10/g in November. From the above results, it was confirmed that 3 species of trematodes metacercaria played an important role in second intermediate hosts infection in Qiqihar region. Studying the morphological characteristics and sequencing the ITS2 gene for a phylogenetic tree of them will be useful for future molecular evolution, biology and ecology of trematode metacercariae.